5
$\begingroup$

I've worked on the following problem and have a solution (included below), but I would like to know if there are any other solutions to this problem, particularly more elegant solutions that apply well known inequalities that I've overlooked.

QUESTION: Suppose we have a random variable s.t. $P(a<X<b) =1$ where $0 < a < X < b$ , $a$ and $b$ both positive constants.

Show that $$E(X)E\left(\frac{1}{X}\right) \le \frac{(a+b)^2}{4ab}$$

Hint: find constant c and d s.t. $\frac{1}{x} \le cx+d$ when $a<x<b$, and argue that then we shall have $E(\frac{1}{X}) \le cE(X)+d$

MY SOLUTION: For a line $cx+d$ that cuts through $\frac{1}{X}$ at the points $x=a$ and $x = b$, it's easy to show that $ c = - \frac{1}{ab} $ and $d = \frac{a+b}{ab} $,

$$ E\left(\frac{1}{X}\right) \le - \frac{1}{ab} E(X) + \frac{a+b}{ab} $$

$$ abE\left(\frac{1}{X}\right) + E(X) \le (a+b) $$

and because both sides of the inequality are positive, it follows that:

$$ \left(abE\left(\frac{1}{X}\right) + E(X)\right)^2 \le (a+b)^2 $$

$$ (ab)^2E\left(\frac{1}{X}\right)^2 + 2abE\left(\frac{1}{X}\right)E(X) + E(X)^2 \le (a+b)^2 $$

Now, for the LHS, we can see that $2abE\left(\frac{1}{X}\right)E(X) \le (ab)^2E\left(\frac{1}{X}\right)^2 + E(X)^2$

because

$0 \le (ab)^2E\left(\frac{1}{X}\right)^2 - 2ab\,E\left(\frac{1}{X}\right)E(X) + E(X)^2 = \left(ab\,E\left(\frac{1}{X}\right) - E(X)\right)^2 $

So,
$$ 4ab\,E\left(\frac{1}{X}\right)E(X) \le (ab)^2E\left(\frac{1}{X}\right)^2 + 2ab\,E\left(\frac{1}{X}\right)E(X) + E(X)^2 \le (a+b)^2 $$

and therefore:

$$ E\left(\frac{1}{X}\right)E(X) \le \frac{(a+b)^2}{4ab} $$ Q.E.D.

Thanks for any additional solutions you might be able to provide. Cheers!

$\endgroup$
2
$\begingroup$

For any number $x$ such that $0<a\le x\le b$, we have $x-a\ge0$ and $b-x\ge0$, so $$ (x-a)(b-x)\ge0,$$ which rearranges into the equivalent form $$ {ab\over x} + x\le a+b,\tag{1}$$ which is the inequality you obtained earlier. You can slickify the rest of your proof as follows. Let $X$ be a random variable with $0<a\le X\le b$. Use $(1)$ to get: $$m+n\le a+b,$$ where $m:=abE(1/X)$ and $n:=E(X)$ are both positive. Then $$4abE(1/X)E(X) = 4mn=(m+n)^2-(m-n)^2\le(m+n)^2\le(a+b)^2.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.